Curious george rides a bike eaudiobook - Rey, H. A. (Weston Woods, 2007)
In this Curious George classic tale, everyone's favorite monkey gets a new bike and mischief and adventure ensue. George can do all kinds of tricks on his new bicycle—even popping a wheelie! When the Man with the Yellow Hat tells him not to go too far, George gets curious and sets off on a journey through his neighborhood. From helping the paperboy with his route to offering a bugle to an ostrich to helping a bear down from a tree, this classic story will be sure to entertain young audiences.